Efficient Calculation of Regional Synthetic Seismograms - McLaughlin, K. L. (1995)
The general behavior of regional seismograms as a function of source type, depth, distance, and frequency is not generally available in many regions of the world where seismic and human activity has not previously provided an empirical base of earthquakes, nuclear explosions, industrial blasts, mine bumps, and rockbursts. Under these circumstances, it is expected that discrimination practice may rely in part on theoretical transportation of discriminants tested in other regions of the world. In order to perform such a theoretical transport of an empirical discriminant, we must have a theoretical understanding of the behavior of that regional discriminant for both regional crustal structures. This work is intended to serve two objectives; provide more accurate and efficient means to compute, store, and retrieve synthetic regional seismograms for reference layered Earth structures and examine limitations to using layered Earth structures to model principal features of regional seismograms in the presence of lateral heterogeneity. This article is from 'Proceedings of the Annual Seismic Research Symposium on Monitoring a Comprehensive Test Ban Treaty (17th) Held in Scottsdale, Arizona on 12-15 September, 1995', 1996 0607 035, p453.